2020
DOI: 10.35848/1347-4065/aba73c
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of microstructure at degraded local area in Ni-multilayer ceramic capacitors under highly accelerated life test

Abstract: Microstructures at degraded local areas have been analyzed, using ‘prebreakdown’ multilayer ceramic capacitors (MLCCs), degraded by a highly accelerated life test (HALT). We have investigated influencing factors of the local microstructures on the lifetime of MLCCs. We have fabricated two lots of the MLCCs, sintered under different temperatures. The degraded local areas have shown some large grains exist, while other normal areas have not. Analyses at the degraded local area revealed a clear correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For instance, microstructure heterogeneity has been reported to cause degradation of MLCCs; by visualizing electrically degraded areas in MLCCs, Sada et al 11 showed that a thinner dielectric layer caused early failure. Nagayoshi et al 12 reported that some large grains were observed in the degraded areas. Samantaray et al 13,14 showed by the finite element method that electrode porosity and roughness in MLCCs could lead to a higher local electric field and leakage current.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, microstructure heterogeneity has been reported to cause degradation of MLCCs; by visualizing electrically degraded areas in MLCCs, Sada et al 11 showed that a thinner dielectric layer caused early failure. Nagayoshi et al 12 reported that some large grains were observed in the degraded areas. Samantaray et al 13,14 showed by the finite element method that electrode porosity and roughness in MLCCs could lead to a higher local electric field and leakage current.…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6] The oxygen vacancies migration from the anode to the cathode under the electric fields plays an important role in the resistance degradation of BaTiO 3 -based MLCCs, which can be usually measured by the thermally stimulated depolarization current (TSDC) method. [7][8][9][10] The previous TSDC studies during the highly accelerated lifetime test (HALT) demonstrated that oxygen vacancies migration dynamics, first, move to the grains and accumulate at the grain boundaries, then migrate across it and pile up close to the cathode, and finally, give rise to a remarkable degradation of the insulation resistance in MLCCs. As a result, understanding the fundamental mechanism between the oxygen vacancies migration process and the electric degradation evolution is very important.…”
Section: Introductionmentioning
confidence: 99%
“…45,46) BiFeO 3 has an extraordinary large P s of 80-100 μC cm −2 along [111] c in rhombohedral R3c symmetry 47,48) (the subscript "c" denotes pseudocubic). Moreover, BiFeO 3 has a Curie temperature (T C ) of 830 °C, 47,48) which is much higher than that of PbTiO 3 (495 °C49) ) Barium titanate, BaTiO 3 , play an essential role for ceramic capacitor applications 50,51) and also for ferroelectricderived functions. [52][53][54][55][56] In tetragonal P4mm symmetry, Ti and Ba are displaced cooperatively along the polar c axis, leading to a P s of 26-29 μC cm −2 .…”
Section: Introductionmentioning
confidence: 99%